Retracted: Chemical Compound Analysis of Syzygium myrtifolium Essential Oil and Molecular Docking Analysis on Phenylalanine Hydroxylase Enzyme - Hamidi, Zikri (Universitas Gadjah Mada, 2025)
Essential oil from the red shoot plant (Syzygium myrtifolium) had high potential as a non-timber forest product. Therefore, this research aimed to evaluate the effect of leaves storage duration on oil yield, essential oil quality, and compliance with the Indonesian National Standard (SNI) 06-237-2006 for clove leaf oil. This research performed steam distillation to produce essential oil from fresh leaves, leaves stored for 24 hours, and leaves stored for 48 hours. The results showed that the highest essential oil yield was obtained from the 24-hour stored leaves at 0.204%, in line with the SNI 06-237-2006. The Gas Chromatography-Mass Spectrometry (GC-MS) analysis showed that the main compounds in the product were beta-pinene (39.09%) and caryophyllene (23.74%). Based on the in silico results from molecular docking, there was a strong interaction between the essential oil compounds and the enzyme phenylalanine hydroxylase. In addition, humulene, ledene, and caryophyllene exhibited the highest binding affinities due to the molecular stability of the enzyme at residues Phe A:254 and Tyr A:325. The current research opened opportunities for developing essential oil-based products for health applications.